Household Sanitation as a Diarrhea Driving Factor of Under-Five Children in Bojonegoro Regency - Taufik Imadudin; Zida Husnina; Retno Adriyani (Universitas Airlangga, 2021)
Introduction: Diarrhea incidence in children under five increases by 11% in Indonesia during 2013 - 2018 that could be driven by poor environmental sanitation. This study examined the relationship between environmental sanitation with diarrhea incidence in children under five. Methods: This study was an observational study with a cross-sectional design and used a total sampling technique of 81 underfive children. Primary data were collected by conducting interviews with parents using a structured questionnaire guideline and observation, including the source of drinking water, availability of healthy latrine, floor condition, and lighting. A Chi-square test (α = 0.05) was conducted to analyse the relationship between variables. Results and Discussion: There was a significant correlation between household sanitation and diarrhea incidence in under-five children (p = 0.040; PR = 1.202 [95% CI 0.987 – 1.463]). Conclusion: Poor household sanitation can be a driving factor in diarrhea incidence in under-five children, where households categorised as good sanitation have 1.2 times lower risk than poor sanitation